Isola Di Terra Nuova - Coronelli, Vincenzo, 1650-1718 ([Venice], 1689)
Black and white. Relief shown pictorially. Includes five bar scales: Italian miles, "Leghe d'un horadicamino," French leagues, English leagues, and German leagues. "Scoperta da Gio. Cabota Veneto con suo figliuolo Sebastiano l'an 1596, 24 Giugno á hore 12" (title). With separate maps on same sheet, drawn in the same style: Le Bermude -- Isola di Mayen -- Frislanda [Iceland?]. CNS map no. 224.